[Não] Trânsito religioso de homens: uma análise da religiosidade de pacientes mediante o diagnóstico oncológico positivo. - Lacerda, Débora Maia (2013)
The current religious landscape is a consequence of modernity and reflects its adaptations on man. According to recent bibliographies, religions have lost their legitimating power in society, ie, they are no longer a crucial item, becoming one more factor in the choices of human beings before the current sociocultural context. Amid the daily difficulties faced by modern subjects, health issues and, specifically, problems of oncological character are present. The aim of this research is the religious transit of men and the influence of their religiousness before the confirmation or indication of a positive oncological diagnosis. Questionnaires were applied to 22 male patients, who were being treated in Napoleão Laureano Hospital. The questions were divided per profile (personal, socioeconomic, pathological and religious), and sought to investigate whether the hope for healing had some religious investment. After final analysis it was found that there's religious "no way" among men from Paraíba addressed in this study and it was evident the predominance of popular Catholicism and its religious tradition. In order to support the research, a theoretical survey was done on the concept of religion and how it is through the prism of modernity, on the popular Catholicism in the Northeast and on the relationship between spirituality and health. For data comparison, surveys conducted that evidenced the religious transit and pointed the coping of chronic diseases through spiritual resources (personal faith, prayers etc.) were also raised.